Observations of meteoritic material and implications for aerosol nucleation in the winter Arctic lower stratosphere derived from in situ particle measurements - Curtius, J.; Weigel, R.; Vössing, H.-J.; Wernli, H.; Werner, A.; Volk, C.-M.; Konopka, P.; Krebsbach, M.; Schiller, C.; Roiger, Anke; Schlager, H.; Dreiling, V.; et al. (HAL CCSD, 2005)
International audience Number concentrations of total and non-volatile aerosol particles with size diameters >0.01 µm as well as particle size distributions (0.4?23 µm diameter) were measured in situ in the Arctic lower stratosphere (10?20.5 km altitude). The measurements were obtained during the campaigns European Polar Stratospheric Cloud and Lee Wave Experiment (EUPLEX) and Envisat-Arctic-Validation (EAV). The campaigns were based in Kiruna, Sweden, and took place from January to March 2003. Measurements were conducted onboard the Russian high-altitude research aircraft Geophysica using the low-pressure Condensation Nucleus Counter COPAS (COndensation PArticle Counter System) and a modified FSSP 300 (Forward Scattering Spectrometer Probe). Around 18?20 km altitude typical total particle number concentrations n t range at 10?20 cm ?3 (ambient conditions). Correlations with the trace gases nitrous oxide (N 2 O) and trichlorofluoromethane (CFC-11) are discussed. Inside the polar vortex the total number of particles >0.01 µm increases with potential temperature while N 2 O is decreasing which indicates a source of particles in the above polar stratosphere or mesosphere. A separate channel of the COPAS instrument measures the fraction of aerosol particles non-volatile at 250°C. Inside the polar vortex a much higher fraction of particles contained non-volatile residues than outside the vortex (~24% outside vortex). This is most likely due to a strongly increased fraction of meteoritic material in the particles which is transported downward from the mesosphere inside the polar vortex. The high fraction of non-volatile residual particles gives therefore experimental evidence for downward transport of mesospheric air inside the polar vortex. It is also shown that the fraction of non-volatile residual particles serves directly as a suitable experimental vortex tracer. Nanometer-sized meteoritic smoke particles may also serve as nuclei for the condensation of gaseous sulfuric acid and water in the polar vortex ...